ANTECEDENT AND CONSEQUENCE FOR ACCOUNTING INFORMATION QUALITY ON INDONESIAN SMEs - Wita Ramadhanti; Kurniawan Kurniawan; Mukhrodin Mukhrodin; Sri Murni Setiyawati (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2019)
This research intended to observe the Accounting Information Quality during 2018, first year implementation of Indonesian Financial Accounting Standard for Micro Small and Medium Entity (SAK EMKM). This is a quantitative research using survey. The objects are Micro, Small and Medium Enterprises in Indonesia. Data is analyze using path analysis. Independent variables are financial literacy, Tax authority pressure, external consultant, Adoption of Marketing information technology. Dependent variables are Accounting Information Quality and Credit Access. The results show that Tax authority pressure and external consultant hiring has positive effect on Accounting Information Quality. Accounting Information Quality has effect on Credit Access. Therefore, further test reveal that Accounting Information Quality do not have mediating role between in the relations independent variables and Credit Access